E-government in Malaysia: Technology adoption by local government employees - Abdul Wahi, Nur Syuhaini; Berényi, László (Vezetéstudomány / Budapest Management Review, 2024)
The proper adoption of technology by users is an essential factor in the success of technological developments. In the public sector, ensuring this deserves particular attention. This study investigates the adoption of a generic e-government system (e-PBT) through a questionnaire survey of Malaysian municipalities. It aims to identify the influencing factors and contribute to developing an integrated framework model. The results demonstrate the usefulness of the models included for further research. The 609-item sample shows better than average adoption rates, although significant differences were found by age, gender, work experience, and type of municipality. Those with higher age and more work experience have lower confidence levels in the system, and those in the districts have higher acceptance levels than those in the cities. Such differences in acceptance can be seen as a significant barrier to dynamic development, and a single training and motivation strategy is insufficient to solve the problems.